PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA PADA KARYAWAN HARIAN SKT MEGAWON II PT. DJARUM KUDUS - Tintami, Lila; Pradhanawati, Ari; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2013)
Human resources is a very important thing for a company because it is people who make a plan, organize, process and control any existing activity on that company's human resources should have a good quality performance to achieve maximum profits. Since the establishment of a company whether consciously or not, a leader certainly laid a foundation of organizational culture that is used as a basis for implementing performance. In addition, transformational leadership style is also required by the management to be able to influence employees to work well. Based on the data obtained, the percentage of absenteeism is increasing, the number of production decreases and the number of cigarettes disability criteria increases. From this, efforts should be made to improve the performance of employees through work discipline. This study aimed to determine the influence of the variable of organizational culture and transformational leadership styles on employee performance through employee discipline PT. SKT Megawon II Djarum Kudus. The study population was a daily part of the production employees totaling 66 people. This research used a census approach, where all members of the population used as a respondent. Measurement scales using Likert scale. In the analysis of the data using simple linear regression and multiple regression test with SPSS 16.00. Based on the survey results revealed that organizational culture, transformational leadership style and work discipline positive effect on employee performance, either partially or simultaneously. The conclusion of this research that simultaneous testing showed that the influence of organizational culture, transformational leadership style and work discipline on employee performance is 84.9%. The advice can be given to PT. Djarum SKT Megawon II Kudus is improved organizational culture found on the company and transformational leadership style which is owned by the management to be done by increasing working discipline in order to reach maximum performance.